2017
DOI: 10.1007/s13311-016-0508-5
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Bulbar Function in Amyotrophic Lateral Sclerosis: The Nuedexta Treatment Trial

Abstract: The goal of this randomized, blinded, crossover clinical trial was to determine whether Nuedexta (dextromethorphan and quinidine) enhanced speech, swallowing, and salivation in patients with ALS. Sixty patients with amyotrophic lateral sclerosis (ALS) received either Nuedexta or placebo for 28 to 30 days, followed by a 10 to 15-day washout period. Subsequently, patients were switched to the opposite treatment arm for the remaining days of the trial. The primary endpoint was a reduction in the self-report Cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 34 publications
(33 reference statements)
2
74
1
3
Order By: Relevance
“…Our prior work has also demonstrated the poor diagnostic accuracy of clinician‐based detection of early bulbar involvement with a false‐positive rate as high as 39% . Our expectation for detecting significant clinical effects on speech in the current study, however, was low because the subgroup of participants studied had, by chance, less severe bulbar dysfunction at baseline than many of the participants in the parent trial and as a group were less responsive to DM/Q treatment . These mixed findings between clinical and quantitative endpoints underscore the ongoing challenges with choosing endpoints for clinical trials that target bulbar motor functions such as speech and swallowing.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Our prior work has also demonstrated the poor diagnostic accuracy of clinician‐based detection of early bulbar involvement with a false‐positive rate as high as 39% . Our expectation for detecting significant clinical effects on speech in the current study, however, was low because the subgroup of participants studied had, by chance, less severe bulbar dysfunction at baseline than many of the participants in the parent trial and as a group were less responsive to DM/Q treatment . These mixed findings between clinical and quantitative endpoints underscore the ongoing challenges with choosing endpoints for clinical trials that target bulbar motor functions such as speech and swallowing.…”
Section: Discussionmentioning
confidence: 69%
“…A full list of the inclusion/exclusion criteria applied in the DM/Q clinical trial is provided in the report by Smith et al . .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Historically, ALS trials have emphasized survival. On a background of failed trials, Nuedexta has been shown to improve speech and swallowing in a double-blind treatment trial [15]. The endpoint of this Phase 2 study was a self-report scale [Center for Neurologic Study Bulbar Function Scale (CNS-BFS)] that proved to be more sensitive to a treatment effect than commonly used measures, such as timed speech and swallowing.…”
Section: Introductionmentioning
confidence: 99%